A rotor-aerodynamics-based wind estimation method using a quadrotor. (9th January 2018) - Song, Yao; Luo, Bing; Meng, Qing-Hao
Abstract: Attempts to estimate horizontal wind by the quadrotor are reviewed. Wind estimations are realized by utilizing the quadrotor's thrust change, which is caused by the wind's effect on the rotors. The basis of the wind estimation method is the aerodynamic formula for the rotor's thrust, which is verified and calibrated by experiments. A hardware-in-the-loop simulation (HILS) system was built as a testbed; its dynamic model and control structure are demonstrated. Verification experiments on the HILS system proved that the wind estimation method was effective.